Role and Place of Electronic Trading Platform Warehouses in Central Asia (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article examines the role of warehouses on electronic trading platforms (ETP) in Central Asia, their significance for the development of the digital economy of the region. Current trends and challenges faced by ETPs in Kazakhstan, Uzbekistan, Tajikistan and other countries in the region are analyzed. The main characteristics of warehouse systems are covered, including the use of modern warehouse management technologies and robotic systems. Development strategies, the need for investment in infrastructure and personnel training are discussed. The prospects for further development of warehouse systems on ETP are explored in the context of integration into global trade flows and increasing the competitiveness of regional economies [1].